2020
DOI: 10.3389/fendo.2020.00090
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between Lymph Node Stage and Clinical Prognosis in Thyroid Cancer

Abstract: Purpose: To investigate the association between lymph node (N) stage and clinical outcome in thyroid cancer patients with initial distant metastasis. Methods: A total of 3,198 cases (1,435 males and 1,763 females) between 2004 and 2015 with initial distant metastasis were obtained from the surveillance, epidemiology, and end results (SEER) database. Patients with a median follow up time of 13 months and a median age of 66 years were analyzed. A total of 1,407 cases had detailed information regarding the four m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 34 publications
1
28
0
Order By: Relevance
“…However, the incidence and recurrence rate of PTC is gradually increasing throughout the world [2,3]. Several works of literature have reported the involvement of central cervical lymph node metastasis (CLNM) and lateral cervical lymph node metastasis (LLNM) with PTC patients, and 80% of long-term recurrence cases have locoregional cervical lymph nodes metastasis (LNM)(pN1) [4][5][6]. In addition, several studies have reported that LNM is a reliable predictor of recurrence [7,8] and poor prognosis [5,9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the incidence and recurrence rate of PTC is gradually increasing throughout the world [2,3]. Several works of literature have reported the involvement of central cervical lymph node metastasis (CLNM) and lateral cervical lymph node metastasis (LLNM) with PTC patients, and 80% of long-term recurrence cases have locoregional cervical lymph nodes metastasis (LNM)(pN1) [4][5][6]. In addition, several studies have reported that LNM is a reliable predictor of recurrence [7,8] and poor prognosis [5,9].…”
Section: Introductionmentioning
confidence: 99%
“…Several works of literature have reported the involvement of central cervical lymph node metastasis (CLNM) and lateral cervical lymph node metastasis (LLNM) with PTC patients, and 80% of long-term recurrence cases have locoregional cervical lymph nodes metastasis (LNM)(pN1) [4][5][6]. In addition, several studies have reported that LNM is a reliable predictor of recurrence [7,8] and poor prognosis [5,9]. However, many researchers [7,10] conducted meta-analyses on the risk factors of LNM and found that the risk factors of LNM in PTC patients were inconsistent across different studies.…”
Section: Introductionmentioning
confidence: 99%
“…Thyroid cancer arises from the follicles or thyroid cells adjacent to the follicles. Despite the decrease in thyroid cancer-related morbidity in recent decades (35), the incidence rate of thyroid cancer is increasing rapidly and thyroid cancer represents a considerable medical burden (36)(37)(38). Surgery, radiation therapy, and chemotherapy are common treatments for thyroid cancer; however, the prognosis for patients with thyroid cancer remains poor (39,40).…”
Section: Txnip and Thyroid Cancermentioning
confidence: 99%
“…Notably, the AJCC‐v7 staging system was based on whether a tumour has extrathyroidal extension and distant metastasis, 8 while the AJCC‐v8 presents a revision to the AJCC‐v7 by adding lymph node status as a staging element 7 . However, current evidences on the association between lymph node status and survival of ATC remain limited and have failed to figure out the association between LNM and prognosis of ATC 9–11 . Therefore, the prognostic predictive value of LNM still needs to be verified, and the survival predictive ability of AJCC‐v8 staging system with lymph node status served as the grading standard also needs to be evaluated urgently.…”
Section: Introductionmentioning
confidence: 99%